Awareness about Gynecological Cancers amongst Tribal Females - Jha, Neha; Panot, Anita H; Singh, Upendra (Asian Pacific Journal of Cancer Care, 2020)
Background: Gender differences are engrained in our culture and are evident when perceiving women’s health and ill health. Health issues of women are of great importance in a society as it directly impacts the fabric of family and society. With limited access to education or employment, high illiteracy rates and increasing poverty levels health improvements for women are quite difficult in developing countries including India. There is a significant lack of official data on gynecological cancers further for women from tribal population which is important for advocacy and public health care planning. Aim: Study aimed at assessing awareness of gynecological cancers amongst tribal females in Borivali Taluka of Mumbai, Maharashtra. Methodology: The research is a descriptive study with a cross-sectional research design. 100 tribal female comprised the total sample. Result: Significant lack of awareness about the Gynecological cancers was seen in the tribal respondents of Aarey circle of Borivalli Taluka, Mumbai regarding the symptoms, treatment, and preventive measures of gynecological cancers. Conclusion: It is evident from previous as well as current study several factors are responsible for poor awareness about gynecological cancers among marginalized tribal respondents.